Fermented milk containing a potential probiotic Lactobacillus rhamnosus SD11 with maltitol reduces Streptococcus mutans: A double-blind, randomized, controlled study - Nuntiya Pahumunto; Supatcharin Piwat; Surasawadee Chanvitan; Wiboon Ongwande; Supansa Uraipan; Rawee Teanpaisan (Elsevier, 2020)
Background/purpose: Sucrose has been considered as a cariogenic substrate due to large amounts of acid production after fermentation by certain oral bacteria, thus sugar alcohols are often used to replace sucrose. The aims of this study were to investigate the effect of maltitol on the growth and acid production of Streptococcus mutans and Lactobacillus rhamnosus-SD11 compared to various sugars, and to examine whether the fermented milk containing a potential probiotic L. rhamnosus-SD11 with maltitol could reduce S. mutans. Materials and methods: The acid production of tested sugars by cariogenic S. mutans was measured using pH meter. In a clinical trial, 123 children were recruited and randomly assigned to either the probiotic- or control-fermented milk, once daily for 4 weeks. The target bacteria levels in the saliva were examined using a real-time PCR at baseline, 4 and 8 weeks. The oral examination was recorded at the baseline and 8 weeks. Results: The results showed that maltitol exhibited less acid production than simple sugars. In the clinical trial, a significant reduction of salivary total streptococci and S. mutans occurred, while the levels of salivary lactobacilli significantly increased in the probiotic group compared to the control group after receiving the probiotic fermented milk. Conclusion: The daily consumption of the fermented milk containing L. rhamnosus-SD11 with maltitol had beneficial effects on oral health by reducing salivary S. mutans. Thus, the substitution of simple sugars by maltitol in dairy products containing L. rhamnosus-SD11 may be an alternative way to prevent the risk of caries.